ĐÁNH GIÁ KHẢ NĂNG LÀM VIỆC CỦA TẤM TÁI SINH KHÔNG KHÍ DO VIỆT NAM SẢN XUẤT TRÊN ĐỘNG VẬT THỰC NGHIỆM - Nguyễn, Hoàng Ngân; Vương, Văn Trường; Hà, Ngọc Thiện; Phạm, Duy Nam (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
ASSESSMENT OF WORKING ABILITY OF THE AIR REGENERATION PLATES IN ANIMAL MODELThe results of the experiments showed that with 6 grams of air revitalization plate per 20 grams of mice the average lifetime of mice were 400.50±24.53 min in comparison with 21.25±2.25 min of the control group. The O2 concentration greater than 19.0% and the CO2 concentration less than 1.3% had been maintained by air revitalization plates for 3 hours (in 200 ml testing box). It was found that the quality of air regeneration plate in this study was similar to one manufactured in Russia.